Assessing the Impact of Web-Based e-Performance Applications on Employee Motivation and Discipline: A Quantitative Study in Batanghari Regency - Naibaho, Ronald; Ahmad Asyhadi; Gunardi; Mardiana (Quantitative Economics and Management Studies, 2025)
This study aims to analyze the effect of using the web-based e-Performance (e-Kinerja) application on the motivation and work discipline of Civil Servants (ASN) in Batanghari Regency. A quantitative approach was employed in this study using an explanatory research design. Data were collected through questionnaires distributed to 187 civil servants across various Regional Government Organizations (OPD), and analyzed using multiple linear regression. The validity and reliability tests showed that all research instruments were valid and reliable. Classical assumption tests also indicated that the data met the requirements of normality, showed no multicollinearity, and were free from heteroscedasticity. The results revealed that the use of the e-Performance application had a positive and significant influence, both simultaneously and partially, on the motivation and work discipline of civil servants. The coefficient of determination (R²) indicated that 36.2% of the variance in motivation and 32.9% of the variance in work discipline could be explained by the use of the e-Performance variable. This application is considered effective in increasing employee expectations regarding performance incentives and strengthening data-based supervision in shaping more orderly and professional work behavior. Furthermore, e-Performance contributes to the transformation of civil servant work culture towards a more transparent, accountable, and results-oriented bureaucracy. These findings offer theoretical implications for the enhancement of technology-based performance management literature, as well as practical implications for local governments in promoting bureaucratic reform through the digitalization of personnel systems.